Walk 4 RIGHT BANK - -, - (project baikal, 2011)
Monument to Emperor Alexander III East-Siberian Railway Residential Building on Rossiyskaya Street Monument to Law Enforcement Soldiers – the Ministry of Internal Affairs Officers Killed on Military Duty